Hydrothermal in situ preparation of TiO 2 particles onto poly(lactic acid) electrospun nanofibres - Gupta K.K.; Mishra P.K.; Srivastava P.; Gangwar M.; Nath G.; Maiti P. (My University, 2025)
The novel poly(lactic acid) (PLA)/TiO 2 hybrid nanofibres are produced via electrospinning technique. Hydrolysed titanium precursor has been electrosprayed simultaneously on the continuous electrospun PLA nanofibres surface. The adhered amorphous titania has been transformed into TiO 2 particle through hydrothermal treatment for different times. The phase structure has been worked out using XRD, FTIR, XPS and Raman spectroscopy. The predominant phase is anatase with a small extent of brookite phase after the hydrothermal treatment. The size and location of TiO 2 particle have been determined using SEM micrographs. The orderness of the PLA crystallites has been checked using XRD patterns before and after hydrothermal treatment. UV absorption capability of the titania coated nanofibres has been enhanced to a significant level. The antimicrobial activity of the hybrids has been verified using two different microorganisms (gram negative Escherichia coli and gram positive Staphylococcus aureus bacteria) and 70% reduction of antimicrobial activity has been reported. © 2012 Elsevier B.V. All rights reserved.